al-Nashr li-fawa'id surah al-`Asr lil-Imam Muhammad ibn `Ali al-Shawkani (D 1250H) : dirasah wa tahqiq = al-Nashr li fawa'id surah al-Asr by Imam Muhammad bin Ali bin Muhammad al-Shawkani : text and analysis / Mohamed Hassan Saeed Ali - Ali, Mohamed Hassan Saeed (2009)
This is a postgraduate dissertation in the field of Tafsir entitled al-Nasyr li Fawaid Surah al-‘Asr by Imam Muhammad bin Ali al-Syawkani (w.1250) : Research and Text Analysis. This Tafsir discusses about surah al-‘Asr which has indication and benefits needed by the public and the general society. This is the basic needs for researchers to build their research and text analysis regarding the manuscript. The research has its introduction, two research parts and a closing part with index. The first part of the research has three discussions which are the profile of the writer, thematic analysis and also the manuscript research. The second part is a discussion on the ideal text analysis and the outcome analysis of the research. This research revises the text analysis done previously and made a conclusion that there are many mistakes, left out and text extension apart from almost all of the previous researches had only used one manuscript as its main reference. On the other hand, this research refers to two different manuscripts and also added its own manuscript research to its whole process of research. This research found out that the tafsir of surah al-‘Asr in Fath al-Qadir by the author was too simple and different with his tafsir in this manuscript.